2006
DOI: 10.1002/ijc.21946
|View full text |Cite
|
Sign up to set email alerts
|

Adulthood consumption of preserved and nonpreserved vegetables and the risk of nasopharyngeal carcinoma: A systematic review

Abstract: The incidence rates of nasopharyngeal carcinoma (NPC) are dramatically higher in certain regions of Asia compared to the rest of the world. Few risk factors for NPC are known; however, in contrast to the hypothesized health benefits of nonpreserved vegetables, it is thought that preserved vegetable intake may play a role in contributing to the higher incidence of NPC in high-risk regions. Therefore, the purpose of this study was to systematically review the epidemiologic evidence on the associations between ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…In studies of Chinese populations, the relative risk of NPC associated with weekly consumption, compared with no or rare consumption, generally ranged from 1.4 to 3.2, whereas that for daily consumption ranged from 1.8 to 7.5 (136)(137)(138)(139)(140)(141). NPC risk is also elevated in association with other preserved food items, including meats, eggs, fruits, and vegetables, in southern Chinese, Southeast Asians, North Africans/Middle Easterners, and Arctic natives (38,39,(138)(139)(140)(141)(142)(143)(144)(145)(146)(147), as well as in low-incidence northern Chinese (148) and the U.S. population (excluding type I NPC; ref. 149).…”
Section: Risk Factorsmentioning
confidence: 99%
“…In studies of Chinese populations, the relative risk of NPC associated with weekly consumption, compared with no or rare consumption, generally ranged from 1.4 to 3.2, whereas that for daily consumption ranged from 1.8 to 7.5 (136)(137)(138)(139)(140)(141). NPC risk is also elevated in association with other preserved food items, including meats, eggs, fruits, and vegetables, in southern Chinese, Southeast Asians, North Africans/Middle Easterners, and Arctic natives (38,39,(138)(139)(140)(141)(142)(143)(144)(145)(146)(147), as well as in low-incidence northern Chinese (148) and the U.S. population (excluding type I NPC; ref. 149).…”
Section: Risk Factorsmentioning
confidence: 99%
“…This indicates that consumption frequency of salt-preserved fish is associated with the risk of NPC. However, elevated NPC risk is also associated with other preserved food items, including meats, eggs, fruits, and vegetables [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Epidemiology Of Nasopharyngeal Carcinomamentioning
confidence: 99%
“…Furthermore, salted fish is a traditional weaning food and is fed early and frequently to infants, especially in the Cantonese population [4,14] and in families of lower socioeconomic status [3,18]. Childhood exposure, especially at weaning, appears to be more strongly related to NPC risk than exposure during adulthood [3,4,14,15,17,[19][20][21]. This dietary association may partly explain the international distribution of NPC incidence.…”
Section: Epidemiology Of Nasopharyngeal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…The EBV-associated, undifferentiated form of NPC exhibits the most consistent association with EBV worldwide and is particularly common in China and Southeast Asia, reaching a peak incidence of ~20-30 cases per 100,000 individuals (3). In addition to genetic predisposition, EBV infection and environmental factors, such as dietary and geographic components, were considered to be important in the aetiology of NPC (4)(5)(6). Previous studies that used quantitative polymerase chain reaction to measure circulating tumor-derived EBV DNA in the blood of NPC patients demonstrated that the level of pre-treatment EBV DNA was significantly associated with overall survival and that post-treatment EBV DNA levels predicted progression-free and overall survival (7,8).…”
Section: Introductionmentioning
confidence: 99%